Discharge Behavior of Tungsten(VI) Oxide Cathodes in Medium-Temperature Lithium Batteries for Borehole Applications - Wang1, Z.J.; Du1, J.L.; Li1, Z.L.; Wu1, Z. (Asian Journal of Chemistry, 2014)
We have investigated the electrochemical properties of WO3 and Li2WO4 used as cathode materials for medium-temperature (200-300 °C) lithium batteries coupled with binary and ternary nitrate eutectic electrolytes. Discharge tests are performed on the combinations of LiMgB/nitrate/tungsten (VI) oxide cells at a current density of 10 mA·cm-2. In general, compared with Li2WO4 cathode, WO3 presents multistep and more sloping voltage plateaux and much less capacities. Compared with binary LiNO3-KNO3 electrolyte, ternary LiNO3-KNO3-CsNO3 electrolyte shows better kinetic activity. The highest cathode capacity of 397.09 mAh g-1 to a 1V cut-off appears in the LiMgB/LiNO3-KNO3/Li2WO4 cell at 200 °C. The compatibility research between tungsten (VI) oxides and nitrate eutectics indicates that no obvious exothermic reactions occur in the temperature range envisaged. The specific reaction mechanisms of the WO3 and Li2WO4 cathodes are also preliminarily investigated by XRD method.